Disfluencies in Conversation between Student and Staff at Language Center in UIN Raden Intan Lampung (Discourse Analysis) - Ansar, Fithrah Auliya (Universitas Islam Negeri Raden Intan Lampung, 2017)
Conversation is the ideal form of communication. Conversation is a kind of spoken discourse that shows spontaneous communication and full of disfluencies. The disfluencies focuses on fillers, vernacular style and careful style. The aim is to find out the kinds of fillers, vernacular style and careful style used in conversation between student and language center staff in UIN Raden Intan Lampung. The analysis used descriptive qualitative by looking at the previous literature. The result shows that there are 10 fillers used by the speakers, 12 vernacular style, and 4 kinds of careful style. Those things have several functions in each utterance. Most of them to show speaker’s feeling, to make statement less harsh, to include the listener to the conversation, to make the simple statement, to reduce faults in making the statement and also to make the utterance more polite.